Physicochemical and potential prebiotic properties of banana peel pectin: conventional vs. ultrasound and non-thermal plasma extraction - Pereira, Maria Angelica Freitas (2024)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Alimentos, Florianópolis, 2024.